THE IMPORTANCE OF USING ARTIFICIAL INTELLIGENCE TECHNOLOGIES IN ELECTRONIC COMMERCE (Marketing Journal, 2025)
This article is devoted to the topic “Ways and Prospects of Applying Artificial Intelligence Technologies in E -Commerce.” It analyzes the theoretical foundations of e-commerce and artificial intelligence concepts, their evolutionary development stages, and integration mechanisms. The study examines the directions of applying artificial intelligence (AI) technologies in e -commerce, including opportunities for optimizing digital trade processes, automated marketing, customer behavior prediction, recommendatio n systems, and personalized services. Furthermore, the article explores the advantages, existing challenges, and modern development trends of using AI technologies. The findings indicate that the implementation of artificial intelligence in e-commerce not only enhances business efficiency but also strengthens competitiveness, improves consumer experience, and accelerates the digital transformation of the economy.
Keywords: e-commerce; artificial intelligence; digital transformation; recommendation system; automation; business efficiency